A Preliminary Review of Poly(lactic acid)-based Biodegradable Foam and its Techno-economic Model - Yudanto Yusuf Arya; Opaprakasit Pakorn (E3S Web of Conferences, 2023)
Biodegradable polymers using renewable resources with properties that are comparable to bio-based and fossil-based polymer materials at a comparable cost have been studied and developed in an effort to solve environmental issues, especially expanded polystyrene. One potential raw main material to replace EPS is poly(lactic acid), a synthetic polymer made from lactic acid, which is made by fermenting organic materials like sweetcorn, rice, soya, potatoes, or whey. It is used in food and non-food packaging, drug-controlled release, agriculture, automotive, and electronic accessories. Foaming is vital in developing lighter, more cost-effective materials that may be utilized for a range of purposes due to their general features, such as lightweight, good heat, more ductile (elastic), and excellent energy absorption (impact resistance). In this review, different types of foaming processes and their process parameters are focused at. It was written following the procedures outlined in the PRISMA2020 (Preferred Reporting Items for Systematic Reviews and Meta-Analysis) guidelines for conducting a review to reports and evaluating a wide variety of interventions. Furthermore, a sustainable material should focus on the efficacy of its resource consumption and the economic feasibility of the product it creates. An economic feasibility study is also provided in this article aims to evaluate how much profit a production plant can make. The techno-economic model developed in this study yielded a profit on sales of 69.69% and an internal rate of return of 44.0%. Techno-economic modeling favored the commercial use of poly(lactic acid)-based biodegradable foam based on its positive net present value, short payback period, and high internal rate of return.